Optimization of maintenance operations for offshore wind farms - Jasper Steendijk; Wouter Beelaerts van Blokland (Digital Transformation in Maritime and City Logistics: Smart Solutions for Logistics. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 28, 2019)
Purpose: The paper provides insights regarding the optimal maintenance strategies for offshore wind farms. The maintenance strategies distinct from each other with location of the operation base and manner of logistics regarding the vessels. Methodology: The methodology for modelling the transport for maintenance operations for offshore wind farms is done with a discrete event simulation with data regarding offshore maintenance operations provided from a large-scale research. Findings: The paper conclude with the optimal maintenance strategy based on the optimal location of the operation base in combination with the best manner of logistics to achieve the preferred requirements with the least transportation costs within the boundaries and limitations of this research. Originality: There are no current papers regarding the maintenance operations for offshore wind farms located far in the Nord Sea.
urn:nbn:de:gbv:830-882.054581; 10419/209197; https://econpapers.repec.org/RePEc:zbw:hiclpr:28
Keywords: 650; Offshore wind farms; Maintenance strategies; Optimization; Logistics